2021
DOI: 10.3390/rs13234827
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Individual Tree Stem Biomass in an Uneven-Aged Structured Coniferous Forest Using Multispectral LiDAR Data

Abstract: Stem biomass is a fundamental component of the global carbon cycle that is essential for forest productivity estimation. Over the last few decades, Light Detection and Ranging (LiDAR) has proven to be a useful tool for accurate carbon stock and biomass estimation in various biomes. The aim of this study was to investigate the potential of multispectral LiDAR data for the reliable estimation of single-tree total and barkless stem biomass (TSB and BSB) in an uneven-aged structured forest with complex topography.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 136 publications
1
16
0
1
Order By: Relevance
“…Overall, the results demonstrate that both SB and TB can be accurately estimated using LiDAR data and the RF algorithm in a structured forest with trees of different ages. In the case of the SB, the results are in accordance with most published studies that have analysed LiDAR data in different ecosystems (e.g., Allouis, Durrieu, Vega & Couteron, 2013;Cao, Coops, Innes, Dai & She, 2014;Cao et al, 2019;Georgopoulos et al, 2021). Thus, we can consider that SB is well described by the LiDAR-derived height-related metrics.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Overall, the results demonstrate that both SB and TB can be accurately estimated using LiDAR data and the RF algorithm in a structured forest with trees of different ages. In the case of the SB, the results are in accordance with most published studies that have analysed LiDAR data in different ecosystems (e.g., Allouis, Durrieu, Vega & Couteron, 2013;Cao, Coops, Innes, Dai & She, 2014;Cao et al, 2019;Georgopoulos et al, 2021). Thus, we can consider that SB is well described by the LiDAR-derived height-related metrics.…”
Section: Discussionsupporting
confidence: 89%
“…If we compare the results with those of studies carried out in the same forest using single-tree detection methods, it can be observed that the EABA approach resulted in slightly worse biomass estimation accuracy (in both SB and TB) (Georgopoulos et al, 2021). This is attributable to the various co-registration and position errors that can easily occur between the ground and Airborne Laser Scanning (ALS) statistics, which can shift the plot sides in different directions.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations